Community-University Partnerships for Local Impact: Advancing Sustainability Through Place-Based Education - Paola Ardiles Gamboa; Rachel Nelson; Simran Purewal; Henrietta Ezegbe; Anna Mathewson; Terri Rutty; Chandana Unnithan; David Zandvliet (The University of Alabama, 2023)
Due to growing demands for experiential learning opportunities and the desire to better prepare students for "real-world" decision-making, community-university partnerships have become novel and experimental spaces within postsecondary institutions. This case study explores a 3-year community-academic partnership pilot designed to provide place-based education experiences around sustainability in an urban North American context. Students' experiences in the pilot program were examined using document reviews, interviews, and online surveys. This paper reports on student learning in relation to civic engagement and place-based education. It also explores how community-academic partnerships can be leveraged to advance sustainability goals at the municipal level, based on a framework encompassing cultural, social, and environmental dimensions of sustainability. The results suggest that the community-academic partnership provided important place-based learning opportunities that both fostered civic engagement and enabled the application of ideas about activism and action competency to support the municipality's holistic sustainability goals. Further analysis of the pilot applying a set of principles related to community-academic partnerships is used to draw insights and identify both the benefits and challenges of the partnership for the students, faculty, and municipal partners involved.